The Effect of Product Quality, Service Quality and Store Atmosphire on Consumer's Repurchasing Interest at Ruang Kopi Bahagia Fatmawati, South Jakarta - Raihan Aqilla Khalis; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of product quality, service quality and store atmosphere on consumer's repurchasing interest at Ruang Kopi Bahagia Fatmawati South Jakarta. The population in this study used a purposive sampling technique where the population taken was 96 people with a significance level of 95% and a standard deviation of 25%. This study uses primary data with data collection methods through questionnaires distributed to 96 respondents. The data analysis technique uses multiple linear regression analysis and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results showed that product quality had a positive and significant effect on consumer's repurchasing interest at Ruang Kopi Bahagia Fatmawati South Jakarta, service quality had a positive and significant effect onconsumer's repurchasing interest at Ruang Kopi Bahagia Fatmawati South Jakarta, store atmosphere had a positive and significant effect on consumer's repurchasing interest at Ruang Kopi Bahagia Fatmawati South Jakarta.